2020
DOI: 10.3389/fped.2020.598016
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Delivery Mode and Early Childhood Body Mass Index Z-Score Trajectories: A Retrospective Analysis of 2,685 Children From Mothers Aged 18 to 35 Years at Delivery

Abstract: Objective: To investigate the association between cesarean delivery (CD) and trajectory patterns of age- and sex-specific body mass index (BMI) z-score in early childhood.Methods: A retrospective cohort study was conducted among 2,685 children whose maternal age at the time of birth was between 18 and 35 years, and birth data and anthropometric measurement data during their ages 3–60 months were collected. A group-based trajectory modeling approach was used to identify distinct BMI z-score trajectories, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Begum et al ( 31 )showed that the pooled OR of “high level” trajectory in offspring delivered by CS was 1.72 (95% CI: 1.28–2.31) compared with those born via VD. Zhang et al ( 32 ) found that children delivered by CS (without distinguishing ECS and non-ECS) more possibly had a “medium to high increase” trajectory from 3 to 60 months of age and a “low to high increase” trajectory from 3 to 60 months of age. Similar to previous studies, we found an increased possibility of “high level” BMI trajectory in children born via ECS with medical indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Begum et al ( 31 )showed that the pooled OR of “high level” trajectory in offspring delivered by CS was 1.72 (95% CI: 1.28–2.31) compared with those born via VD. Zhang et al ( 32 ) found that children delivered by CS (without distinguishing ECS and non-ECS) more possibly had a “medium to high increase” trajectory from 3 to 60 months of age and a “low to high increase” trajectory from 3 to 60 months of age. Similar to previous studies, we found an increased possibility of “high level” BMI trajectory in children born via ECS with medical indicators.…”
Section: Discussionmentioning
confidence: 99%
“…(5) We also used BMI standard deviation score (BMI SDS) instead of BMI to compare the risk of HBP in different groups with multivariate logistic models. Age-and sex-specific BMI SDS was calculated using the World Health Organization (WHO) child growth charts [25][26][27].…”
Section: Discussionmentioning
confidence: 99%